Strategi Pengelolaan Keuangan Mahasiswa di Tengah Penguatan Dolar AS dan Tren Gaya Hidup Hedonisme - Rudi Alamsyah; Chelsea Lolita Br. Sembiring; Yusrita Br. Pinem; Fadila Ardhana; Dwi Syafitri; Ulen Bangun (Trending: Jurnal Manajemen dan Ekonomi, 2026)
The strengthening of the United States Dollar (USD) against the Indonesian Rupiah has become an economic challenge affecting various aspects of society, including university Students. At the same time, the development of information technology and social media has encouraged the emergence of a Hedonistic Lifestyle trend that influences Students’ consumption patterns. This study aims to analyze Students’ Financial Management strategies in facing the strengthening of the US Dollar and the trend of Hedonistic Lifestyles. The research employs a method with a descriptive qualitative approach. Data were collected through the review of scientific journals, books, and official institutional reports relevant to the research topic. The findings indicate that the strengthening of the US Dollar potentially increases Students’ living costs through rising prices of imported goods and services. Meanwhile, a Hedonistic Lifestyle encourages consumptive behavior that may disrupt Students’ financial stability. Therefore, effective Financial Management strategies are required through improving financial literacy, budgeting, controlling consumptive behavior, establishing emergency funds, and diversifying income sources. These strategies can help Students maintain financial stability and strengthen their financial resilience amid global economic dynamics.